2017
DOI: 10.4269/ajtmh.16-0749
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Behavioral Drivers of Buruli Ulcer Disease in Selected Communities Along the Densu River Basin of Ghana: A Case-Control Study

Abstract: The exact route of transmission of Mycobacterium ulcerans (MU) (causative agent of Buruli ulcer [BU]), risk factors, and reservoir hosts are not clearly known, although it has been identified as an environmental pathogen. This study assessed potential environmental and behavioral risk factors that influence BU infections. We conducted a case-control study where cases were matched by their demographic characteristics and place of residence. A structured questionnaire was administered to solicit information on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
5
13
0
Order By: Relevance
“…Two separate studies have shown that BU lesions mostly occur where the bones are close to the skin (shins, knees, elbows and forearms) [ 21 , 36 ]. We observed a distribution pattern that supports the direct contact with an exposed skin hypothesis as 74.4% of BU lesions were restricted to the limbs; lower limb (59.7%) and upper limb (14.7%) corroborating with several other reported studies [ 37 42 ]. In the African BU endemic regions, the hot weather conditions may be a major contributory factor for this localized lesion restriction as farmers in particular are less likely to wear protective clothes during activities to enhance efficient work output; a behavior that is likely to enhance the exposure of the skin to M .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Two separate studies have shown that BU lesions mostly occur where the bones are close to the skin (shins, knees, elbows and forearms) [ 21 , 36 ]. We observed a distribution pattern that supports the direct contact with an exposed skin hypothesis as 74.4% of BU lesions were restricted to the limbs; lower limb (59.7%) and upper limb (14.7%) corroborating with several other reported studies [ 37 42 ]. In the African BU endemic regions, the hot weather conditions may be a major contributory factor for this localized lesion restriction as farmers in particular are less likely to wear protective clothes during activities to enhance efficient work output; a behavior that is likely to enhance the exposure of the skin to M .…”
Section: Discussionsupporting
confidence: 91%
“…In the African BU endemic regions, the hot weather conditions may be a major contributory factor for this localized lesion restriction as farmers in particular are less likely to wear protective clothes during activities to enhance efficient work output; a behavior that is likely to enhance the exposure of the skin to M . ulcerans in the environment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the incidence rose in Australia, from 32 cases in 2010 to 106 cases recorded in Victoria in 2015 (27). Understanding the epidemiological trends of Buruli ulcer has been obscured by the lack of definite knowledge regarding the reservoirs and modes of transmission of the causative agent, M. ulcerans, in every region of endemicity (19,28,29). Human-tohuman transmission of Buruli ulcer has rarely been reported, suggesting environmental sources, as corroborated by several studies (30).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies brought new insights which contribute to the better understanding of the puzzle of transmission. For example, certain correlations between environmental factors and BU incidence could be shown by researchers from the NMIMR, which confirmed behavioural risk factors for contracting the disease, such as farming in swampy areas or application of leaves on wounds [19]. Sero-epidemiological studies showed that exposure to M. ulcerans increases at an age of about 4 years.…”
Section: Transmissionmentioning
confidence: 80%